Correction to: What to Do and What Not to Do in the Management of Opioid-Induced Constipation: A Choosing Wisely Report - Domenico Alvaro; Augusto Tommaso Caraceni; Flaminia Coluzzi; Walter Gianni; Fabio Lugoboni; Franco Marinangeli; Giuseppe Massazza; Carmine Pinto; Giustino Varrassi (Pain and Therapy, 2020)
The original article can be found online.